Effect of modification techniques on surface of carbon nanofiber as catalyst support - Nguyen Van, T.D. (Trans Tech Publications Ltd, 2014)
The intrinsic surface of carbon nanofiber (CNF) is important for supported catalyst preparation. The surface changes due to various techniques applied such as N2 thermal and HNO3 oxidation methods. The combination of different analyses is to observe the internal structure through Raman spectroscope, textural properties via N2 physisorption and morphology of CNF using transmission electron microscope or through quantification of oxygen containing groups by acid base titration. As results, an extension of residence time increases the amount of amorphous and damages the structure of mesoporous CNF texture unexpectedly. The change from hydrophobic to hydrophilic surface of CNF is due to the growing number of oxygen. The surface area of CNF by HNO3 treatment method produces 115.14m2g which is higher than that of using thermal method. Â© 2014 Trans Tech Publications, Switzerland.